Penerapan Regresi Linear Pada Minat Berwirausaha Mahasiswa Telkom University Surabaya - Nafi’atus Sa’idah, Rizqy Athiyya; Zahra, Aisyah Nabila; Siahaan, Fitri Rayani; Hidayati, Sri (Program Studi Statistika FMIPA Universitas Mulawarman, 2024)
Entrepreneurship is an effort to reduce the problem of unemployment. To build interest in entrepreneurship, it is necessary to analyze factors related to entrepreneurship. In this study, respondents were taken from students of Telkom Institute of Technology Surabaya Information Systems and Digital Business Study Program with factors taken from income expectations, family environment, and entrepreneurship education. This research has important implications in equipping students with entrepreneurial skills and increasing their interest in entrepreneurship. Thus, the results of this study provide a foundation for the development of programs and policies that support the development of entrepreneurship among students. The method used in this study is linear regression with the results showing that income expectation factors, family environment and entrepreneurship education have a positive influence on student entrepreneurial interest both partially and simultaneously